Tingkat Premi, Klaim dan Risk Based Capital (RBC) Berpengaruh Terhadap Profitabilitas Perusahaan Asuransi Syariah - Laila Nursalamah; Zulpahmi Zulpahmi; Faizal Ridwan Zamzany (Universitas Muhammadiyah Prof. DR. HAMKA, 2021)
This research is aimed to knowing the effect of Premium Level, Claims and Risk Based Capital (RBC) on Profitability of Islamic Insurance Companies. Research method is quantitative and the source of the data obtained is secondary data, while the method in the analysis of studies using multiple linier regression analysis. The sampling method used was purposive sampling from 26 islamic insurance companies, 9 companies met the criteria to be the sample.The result showed that the partial Premium Level has a negative and significant effect on profitability, claims have a positive and significant effect on profitability, and Risk Based Capital (RBC) has a negative and significant effect on profitability. Simultaneously, Premium Level, Claims and Risk Based Capital (RBC) variable have a significant to profitability. Thus, it is recommended that sharia insurance companies pay attention to the management and use of premium funds properly through investment so that they are used when the claim burden is high and maintain risk-based capital stability in order to meet obligations and increase the profitability of Islamic insurance companies.